HSA functionalized Gd2O3:Eu3+ nanoparticles as an MRI contrast agent and a potential luminescent probe for Fe3+, Cr3+, and Cu2+ detection in water. (12th August 2020) - Vashistha, Nidhi; Chandra, Abhishek; Singh, Man
Abstract : PVP capped Gd2 O3 :Eu 3+ (PVP@Gd2 O3 :Eu 3+ ) and HSA functionalised PVP@Gd2 O3 :Eu 3+ (HSA@PVP@Gd2 O3 :Eu 3+ ) NPs as fluorescent detection probe for metal ion detection and MRI contrast agent. Abstract : Polyvinylpyrrolidone (PVP) capped rod-shaped europium (Eu 3+ ) doped gadolinium oxide (Gd2 O3 ) nanoparticles (PVP@Gd2 O3 :Eu 3+ NPs) were synthesized by a wet chemical method at 90 °C. NPs were characterised by X-ray diffraction (XRD), high resolution transmission electron microscopy (HR-TEM), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), fluorescence spectroscopy and inductively coupled plasma optical emission spectrometry (ICP-OES). The PVP@Gd2 O3 :Eu 3+ NP surface was then functionalized with human serum albumin (HSA) to form HSA@PVP@Gd2 O3 :Eu 3+ NPs. Both PVP@Gd2 O3 :Eu 3+ NPs and HSA@PVP@Gd2 O3 :Eu 3+ NPs showed strong host sensitized fluorescence in water. The surface functionalization with HSA enhanced the stability of the NPs in both aqueous and biological media. The NPs dispersed in water were highly sensitive towards Fe 3+, Cr 3+ and Cu 2+ ion detection, among various transition and heavy metal ions. The HSA@PVP@Gd2 O3 :Eu 3+ NPs exhibited almost five times lower detection limit for Fe 3+, Cr 3+ and Cu 2+ ions compared to PVP@Gd2 O3 :Eu 3+ NPs. PVP@Gd2 O3 :Eu 3+ NPs were highly selective for a water sample containing >0.667 ppm Fe 3+, Cu 2+, and Cr 3+ ions, while the HSA@PVP@Gd2 O3 :Eu 3+ NPs at <0.667 ppm were highly selective towards Fe 3+ ion sensing. The PVP@Gd2 O3 :Eu 3+ and HSA@PVP@Gd2 O3 :Eu 3+ NPs were employed as contrast agents in MRI with improved longitudinal relaxivity ( r 1 ) values of 6.96 and 6.15 mM −1 s −1, respectively. These values are higher than that of the commercial contrast agent Magnevists. The Gd2 O3 :Eu 3+ NPs were capped with PVP and coated with HSA for surface functionalization as a useful MRI contrast agent and for transition metal ion detection.